IMPLEMENTASI PERATURAN BUPATI NOMOR 31 TAHUN 2008 DALAM PENGELOLAAN PASAR DI KECAMATAN UJUNGBATU KABUPATEN ROKAN HULU - Minarni, Ade; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to describe the implementation of market management in the District Ujungbatu Rokan Hulu. This policy is implemented as Rokan Hulu Government's efforts to take care of the problem in every district government administration in Rokan Hulu in the field of management of the market to achieve the objectives that have been planned. Agenda contained in the decree No. 31 of 2008 on the delegation of authority management and market development to the District. The success of a program is to implement a policy or program policy based on the theory proposed by George C. Edaward III suggests that there are four factors that influence the success of a policy. The usefulness of this study are as material information on how the policy implementers in implementing policies that have been present in the market management in the District Ujungbatu to provide input to the government especially in the implementation of the policy and toknow the shortcomings and obstacles that occur. The method used in this study is qualitative methods of data that can not be realized in the form of figures but rather in the form of an explanation that describes the shape of the state, process, certain events. Data collection techniques using interview techniques and documentation. From the results of the qualitative descriptive data analysis of the implementation is in the district market management policies Ujungbatu categorized Rokan Hulu has not been successful. This is evident from a comparison between the target and the realization in the market levies, the absence of guidance provided to the market management, the absence of strict sanctions for merchants who pay late or do not pay the levy markets, low market awareness trader in pay the levy. Keywords: Implementation, Market Management, dan Regulation